IMPROVING WATER FILTERS AS AN EFFORT TO IMPROVE COASTAL COMMUNITY AWARENESS REGARDING CLEAN WATER SANITATION - Irawati, Heni; Wiharyanto, Dhimas; Taqwa, Amrullah; Achyani, Ratno; Jabarsyah, Abdul; Rachmawani, Dori; Firdaus, Muhammad; Laga, Asbar; Roem, Muhammad; Salim, Gazali; Alawiyah, Tuty; Haryono, M Gandri; Gaffar, Syamsidar; Yushra, Yushra; Yusuf, Muhammad Yusfi; Muhtar, Dian Islamia; Romdoni, Taufiq Ahmad; Kase, Ardy Andreas Bernard; Zunianto, Anang; Susanto, Hermawan (Universitas, 2025)
Abstract Tarakan City has potential groundwater that can be utilized as a source of clean water for the community. However, its utilization is currently constrained by the poor groundwater quality, thus necessitating filtration efforts. A simple technology that can be applied is filtration using waste shells of kapah clams (Meretrix sp.), which are abundantly available in coastal area of Pantai Amal Subdistrict. This activity aims to raise community awareness about the importance of clean water sanitation while providing training on how to utilize kapah clam shells as basic materials for simple water filters. The methods used in this program include public socialization, demonstration of water filter production, and assistance to the community. The filter media used in this process are kapah clam shells combined with activated carbon, quartz sand, and gravel. The application is expected to improve groundwater quality to meet environmental health standards as stipulated in the Regulation of the Minister of Health of the Republic of Indonesia No. 2 of 2023. The result showed that kapah clam shells have been proven effective as a filtration medium, particularly in improving the physical quality of water, and can serve as an alternative solution for communities in accessing suitable clean water. Keywords: groundwater, kapah clam shells (Meretrix sp.), higiene and sanitation, environmental health Abstrak Kota Tarakan memiliki potensi air tanah yang dapat dimanfaatkan sebagai sumber air bersih oleh masyarakat. Namun saat ini pemanfaatannya masih terkendala oleh kualitas air tanah yang belum memenuhi standar baku mutu, sehingga perlu dilakukan upaya penyaringan air. Salah satu teknologi sederhana yang dapat diterapkan adalah filtrasi menggunakan limbah cangkang kerang kapah (Meretrix sp.) yang banyak tersedia di wilayah pesisir, khususnya di Kelurahan Pantai Amal. Kegiatan ini bertujuan untuk meningkatkan kesadaran masyarakat akan pentingnya sanitasi air bersih, sekaligus memberikan pelatihan tentang cara memanfaatkan limbah cangkang kapah sebagai bahan filter air sederhana. Metode yang digunakan dalam kegiatan ini meliputi sosialisasi, demonstrasi pembuatan filter air, serta pendampingan langsung kepada masyarakat. Bahan yang digunakan dalam proses pembuatan filter adalah cangkang kapah yang dikombinasikan dengan arang aktif, pasir kuarsa, dan kerikil. Penggunaan filter sederhana ini diharapkan mampu meningkatkan kualitas air tanah hingga memenuhi standar kesehatan lingkungan yang tertuang dalam Peraturan Menteri Kesehatan Republik Indonesia No. 2 Tahun 2023. Hasil kegiatan menunjukkan bahwa penggunaan limbah cangkang kapah sebagai media filter cukup efektif dalam memperbaiki kualitas air secara fisik dan dapat menjadi solusi alternatif bagi masyarakat dalam mendapatkan air bersih yang layak. Kata Kunci: Air tanah, cangkang kerang kapah (Meretrix sp.), higiene dan sanitasi, kesehatan lingkungan